The use of e-learning in language teaching in higher education - Doğan, Yunus; Bağçeci, Birsen; Talan, Tarik (Nova Science Publishers, Inc., 2024)
This chapter presents information about e-learning and its utilization in foreign language teaching in higher education. E-learning, also known as electronic learning or online learning, refers to the process of acquiring knowledge, skills, and education using electronic technologies such as computers, the internet, and digital media. In the past 20 years, technological advancements have significantly accelerated, especially in the field of Information and Communication Technologies (ICT), leading to the integration of ICT into everyday life as an essential element. Additionally, the development of ICT has resulted in new learning and teaching opportunities, known as online learning, which not only benefits students but also teachers by combining computers and the internet in the educational process. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: e-learning; e-learning in foreign language education; Higher education; Online learning